Neuropsychiatric disease (NPD) clustering in families with Autism Spectrum Disorder (ASD): genetic, epigenetic and environmental issues - Marques, Ana Rita (2017)
Objectives: The aim of this project is to understand the role of epigenetic factors in ASD, with a particular focus on long noncoding lncRNA, miRNA and other regulatory molecules. For this purpose this project has two main specific objectives: 1. To identify lncRNA and miRNA loci implicated in ASD through the analysis of two large datasets with CNV and SNV data from ASD families and controls; 2. To identify genetic variants and modulating epigenetic factors that could lead to differential disease expression by exploring multiplex families in which ASD co-occurs with other NPDs.